Serpulidae (Annelida, Polychaeta) from Patton-Murray Seamounts, Gulf of Alaska, North Pacific Ocean - Kupriyanova, Elena K.; Nishi, Eijiroh (Zootaxa, 2010)
A collection of Serpulidae (Annelida, Polychaeta) from the Patton-Murray Seamounts, Gulf of Alaska, USA contained three species Apomatus voightae n. sp., Bathyvermilia eliasoni n. comb., and Hyalopomatus biformis (Hartman, 1960). Apomatus voightae n. sp. differed from all other Apomatus spp. and from all known serpulid species by very unusual flat and ribbon-like branchial radioles as well by details of chaetal structure. Vermiliopsis eliasoni Zibrowius (1970) previously known from Atlantic and Mediterranean, was transferred to the genus Bathyvermilia Zibrowius, 1973. Hyalopomatus biformis is a deep-sea species distributed in the north-eastern Pacific from Alaska to California, USA. All serpulids were described in detail and their chaetal structure elucidated with the help of scanning electron microscopy. Molecular sequence data (18S rDNA) were aligned to a recently published serpulid data set and maximum parsimony analysis was performed to examine the phylogenetic position of the species and confirm their identification. Hyalopomatus biformis formed a sister group with Laminatubus alvini, Apomatus voightae n. sp. formed a sister group with Apomatus globifer, and Bathyvermilia eliasoni formed a weakly supported polytomy with Chitinopoma serrula, Protula tubularia and Apomatus spp. We briefly discussed biogeographic affinities of the serpulids from the PattonMurray Seamounts in the light of seamount ecology and biogeography.